Adjectivation in Abraham Valdelomar’s Chronicles - Sala, María del Carmen (2020)
Abraham Valdelomar is a renowned writer who also makes journalism. This is evident in the language he used in his chronicles, particularly, in the usage of adjectives. In this paper, four of his chronicles were analized in order to show the patterns of his handling of adjectives. These patterns can be directly linked to two criteria: to specify the described or narrated events and to provide a personal appreciation of them. A double tension is perceived in the author. As a journalist he had to comply with the requirements of a media text whose main purpose is to inform, on the other hand, as a writer he wanted to express his views and feelings regarding what had been described or narrated. This double purpose is resolved in the amount and type of adjectives he uses.